Predicting psychological distress: A cross- sectional study of Malaysian teachers - Ibrahim, R Zirwatul Aida R; Zalam, Wan Zaleha Mohd; Dagang, Mazidah Mohd; Omar , Khatijah; Bakar , Azlina Abu; Mat Ali, Siti Nazilah (International Journal of Psychosocial Rehabilitation, 2020)
Based on the theory underlying the Job Demands-Control (JDC) and Job Demands-Control-Support (JDCS) models, the current study examined the predictors of psychological distress involving job demands, job control and social support. The cross-sectional study designed involved 335 teachers from Kuala Terengganu, a district located on the East Coast of Malaysia. The regression analysis showed that job demands, job control and social support significantly predict psychological distress among teachers. Overall, this study contributes to the corpus of literature by using JDC and JDCS models in the context of the Malaysian culture. Improving job control and social support, reducing job demands considered as important factors to prevent psychological distress among teachers.